El laboratorio como estrategia de aprendizaje de biología con estudiantes de segundo de bachillerato de la Unidad Educativa la Merced período 2024-2025. - Carrillo Cabrera, Carla Abigail (2025)
In the second year of high school at La Merced School, a gap has been identified between the application of theory and practice, which has hindered students' understanding of the subject matter. The main objective of this research was to analyze the use of the laboratory as a learning strategy in Biology classes for second-year high school students at La Merced School during the 2024-2025 academic year. The research methodology employed a mixed approach, with a non-experimental, descriptive design, utilizing both field research and a review of relevant literature. A survey was administered to 90 students from groups A, B, and C of the second year of high school at La Merced School. The results showed that students generally had a positive attitude towards laboratory activities. 53% stated they were willing to collaborate in laboratory activities, and 27% strongly agreed, indicating an active willingness to participate in group work and contribute to the development of experimental activities. Finally, a teaching guide was developed, based on laboratory activities, to enhance students' learning of Biology concepts in the second year of high school.